PERBANDINGAN SYARAT IMPEACHMENT DI DALAM UN- DANG-UNDANG DASAR 1945 DENGAN PEMIKIRAN IMAM AL- MAWARDI - Satriya, Catur Alfath (Journal of Islamic Law Studies, 2021)
After reformation, constitutional structure of Republic of Indonesia has transformed fundamentally. People consultative assembly (MPR) is no longer as the highest of state institution anymore. Further- more, impeachment as one of the feature of presidential government system is regulated in new con- stitution. Before amendment, Indonesia has no rule of impeachment. So, impeachment is only based on political decision not law decision and it is not appropriate with rule of law principle. This article describe the comparison of impeachment requirement in UUD 1945 with impeachment requirement in Imam Al- Mawardi’s thought as a political islamic scholar.